Effects of Climate Change on Soil Organic Matter C and H Isotope Composition in a Mediterranean Savannah (Dehesa): An Assessment Using Py-CSIA - San-Emeterio, Layla M.; Zavala, Lorena M.; Jiménez-Morillo, Nicasio T.; Pérez-Ramos, Ignacio M.; González-Pérez, José A. (Environmental science & technology, 2023)
Dehesas are Mediterranean agro-sylvo-pastoral systems sensitive to climate change. Extreme climate conditions forecasted for Mediterranean areas may change soil C turnover, which is of relevance for soil biogeochemistry modeling. The effect of climate change on soil organic matter (SOM) is investigated in a field experiment mimicking environmental conditions of global change scenarios (soil temperature increase, +2–3 °C, W; rainfall exclusion, 30%, D; a combination of both, W+D). Pyrolysis-compound-specific isotope analysis (Py-CSIA) is used for C and H isotope characterization of SOM compounds and to forecast trends exerted by the induced climate shift. After 2.5 years, significant δ13C and δ2H isotopic enrichments were detected. Observed short- and mid-chain n-alkane δ13C shifts point to an increased microbial SOM reworking in the W treatment; a 2H enrichment of up to 40‰ of lignin methoxyphenols was found when combining W+D treatments under the tree canopy, probably related to H fractionation due to increased soil water evapotranspiration. Our findings indicate that the effect of the tree canopy drives SOM dynamics in dehesas and that, in the short term, foreseen climate change scenarios will exert changes in the SOM dynamics comprising the biogeochemical C and H cycles.